Modelling South Pacific jack mackerel spatial population dynamics and fisheries. (14th November 2017) - Dragon, A.‐C.; Senina, I.; Hintzen, N.T.; Lehodey, P.
Abstract: Since the 1970s, South Pacific jack mackerel ( Trachurus murphyi ) is one of the world's most important commercial exploited fish stock. The peak in the catch was achieved in the 1990s, after which the catch for all fleets steadily decreased due to strong fishing mortality and potentially unfavourable environmental conditions. An application of the ecosystem and fish population model SEAPODYM was developed for this species in the South Pacific Ocean to determine the extent of environmental and fisheries drivers on the stock dynamics. We combined publicly available fishing data, acoustic biomass estimates and expert knowledge to optimise fish population dynamics parameters (habitats, movements, natural and fishing mortality). Despite a large proportion of missing catch over the simulation period, the model provides realistic distributions of biomass, a good fit‐to‐data and is in agreement with the literature. The feeding habitat is predicted to be delineated by water temperature between 15°C for the first cohorts and 8.5°C for the oldest and dissolved oxygen concentration above 1.8 ml/L. Optimal spawning temperature is estimated to 15.57°C (S.E.: 0.75°C). The core habitat is predicted off Central Chile which is also the main fishing ground. There are other areas of higher fish concentration east of New Zealand, in the eastern part of the southern convergence and off Peru and northern Chile. However, there is a clear continuity between these different large sub‐populations. Fishing is predicted to have by far the highest impact, a result that should be reinforced if all fishing mortality could be included.